The effectiveness of nutritional intervention on the athletic of performance non-professional male boxers - Veniamakis, E.; Giovani, D.; Nikolaidis, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The purpose of this study was to assess the effectiveness of a nutritional intervention on athletic performance of male non-professional boxers. Methods: Eight non-professional male boxers (29,4±3,2 age, 77,6±8,6 kg, 39,3±7,5 VO2max) participated in the study, in which they were randomly divided into two groups of four (control group and intervention group). The control group continued their eating habits, as they were until before the study, whereas the intervention group followed a diet for three weeks according to their needs in energy, micro- and macronutrients in combination with the needs of boxing training in order to maintain their current weight. Before and right after the nutritional intervention, anthropometric (weight, height, body composition and body type) and fitness assessment measurements (flexibility, sub-maximal aerobic test (W170), maximal aerobic test (VO2max), speed force test for upper and lower extremities, upper extremities strength test, body core strength test, body core-lower extremities strength test and Wingate test) were conducted to the athletes. For the data analysis a paired-samples t-test and an independent-samples t-test were used. Results: The intervention group showed an increase in VO2max, upper extremities strength, and free-fat mass, with a simultaneous decrease in % body fat. Conclusions: This study showed that the nutritional intervention can improve the athletic performance of non-professional male boxers. More research is needed on this area, as the period of the nutritional intervention was short and also a follow up study is necessary.